EFFECT OF Zanthoxylum acanthopodium DC EXTRACT ON THE INCREASE OF BRAIN CELLS IN THE SUBSTANTIA NIGRA OF WISTAR RATS THAT ARE ROTENONE-INDUCED - hafizha, Shalli; Halim, Binarwan; Chiuman, Linda (The Islamic Education and Multiculturalism Foundation, 2024)
Parkinson's disease (PD) is a neurodegenerative disorder due to the decline of dopaminergic neurons in the substantia nigra, with motor and non-motor symptoms. Oxidative stress, inflammation, and mitochondrial damage play a role in its pathogenesis. andaliman fruit (Zanthoxylum acanthopodium DC), rich in alkaloids and flavonoids, has potential as an antioxidant with neuroprotective effects. The purpose of the study was to determine the effect of andaliman fruit extract (Zanthoxylum acanthopodium DC) on the increase of brain cells in the substantia nigra of rotenone-induced Wistar rats as a Parkinson's model. This research uses an experimental quantitative study with a post-test control group design. Data were analyzed using One Way ANOVA with a significance level of p < 0.05. The results showed that 70% ethanol extract of andaliman fruit (Zanthoxylum acanthopodium DC) can reduce the number of necrosis cells in the brain. On the 29th day, the average number of necrosis cells in each group was 0.4±0.54 (K-), 4.8±0.83 (K+), 4.4±1.14 (P1), 3.4±0.54 (P2), and 1.2±0.44 (P3). The administration of extracts at doses of 150 mg/kgBB, 300 mg/kgBB, and 450 mg/kgBB can increase the regeneration of brain cells that experience necrosis. Histopathological observations showed that 70% ethanol extract of andaliman fruit improved the histological structure of brain cells in the substantia nigra area.